1995
DOI: 10.7901/2169-3358-1995-1-107
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of Oiled Beach Sediments: Assessment of Inorganic and Organic Fertilizers

Abstract: The effects of inorganic (ammonium nitrate and triple superphosphate) and organic (fish bone-meal) fertilizers on the biodegradation rates of Venture condensate within a sand-beach environment were assessed over 333 days. Field results showed that the organic fertilizer stimulated microbial growth and metabolic activity to the greatest extent. However, based on chemical analysis of residual oil concentrations and composition, the application of inorganic fertilizers was the superior bioremediation strategy. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…This is in line with Lee et al, (1995) who reported that organic manures have effects in stimulating crude oil degradation by increasing the total heterotrophic microbial growth and activity. This assertion is true since there was increase in heterotrophic microbial population in this study.…”
Section: Fig 8 Effects Of Treatments On the Soil Potassiumsupporting
confidence: 92%
“…This is in line with Lee et al, (1995) who reported that organic manures have effects in stimulating crude oil degradation by increasing the total heterotrophic microbial growth and activity. This assertion is true since there was increase in heterotrophic microbial population in this study.…”
Section: Fig 8 Effects Of Treatments On the Soil Potassiumsupporting
confidence: 92%
“…Assuming that microbes are present, nutrient availability, especially of nitrogen and phosphorus, appears to be the most common limiting factor (494,526). Laboratory and field experiments with inorganic nitrogen and phosphate fertilizers and organic fertilizers, including fish bones, fish or animal meal, biosurfactants, and bulking agents, have shown success (68,241,371,372,428,446,458,512,635,640).…”
Section: Treatment Of Contaminated Soils and Sludgesmentioning
confidence: 99%
“…In addition, there is now a renewed interest in the advantages of having an organic carbon source within bioremediation agents to promote rapid bacterial growth [36]. This has lead to the recent development and testing of organic fertilizers comprised of fish meal, animal meal, and/or fish bone meal [37,38]. Theoretically, optimal nutrient concentrations can be maintained within oiled sediments for prolonged periods by the internal nutrient regeneration processes coupled with the degradation of these products.…”
Section: Addition Of Nutrientsmentioning
confidence: 99%